Analisis Produktivitas Menggunakan Objective Matrix (OMAX) pada lantai produksi Sigaret Kretek Mesin (SKM) PT. Nikorama Citra Tobacco - Fiqih, Muhamad Nur; Ramdhani, Safarudin (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study is centered on calculating the productivity of the SKM (rolled kretek cigarette) production floor work station of PT. Nikorama Citra Tobacco from 22 January 2024 to 29 February 2024 which aims to measure the level of productivity in the cigarette production process on the SKM production floor, identify key elements that have the greatest impact on the level of productivity achieved, and propose or recommend improvement steps to increase productivity in the production process on the SKM production floor. This research utilizes the objective matrix method (OMAX) by measuring two elements of productivity, namely the element of efficiency and the element of effectiveness. From these two elements of productivity, six measurement ratios are obtained, labor ratio, production output ratio, working hours ratio, defective product ratio, production time ratio. , engine ratio. The results of this research show that the productivity results of the SKM production floor fluctuate up and down due to the instability of the productivity ratio performance value where the highest productivity occurs on February 22 2024 and the worst productivity on January 22 2024, while the best ratio value occurs in the yield ratio. production and worst ratio values ??on machine ratios. The worst ratio value occurs in the machine ratio so improvements need to be made so that the productivity value can be more optimal.